CD68 tumor-associated macrophage marker is not prognostic of clinical outcome in classical Hodgkin lymphoma. Issue 5 (May 2014) - Kayal, Smita; Mathur, Sandeep; Karak, Asis K.; Kumar, Lalit; Sharma, Atul; Bakhshi, Sameer; Raina, Vinod
Abstract A novel biomarker, CD68, which marks tumor-associated macrophages (TAMs) in the microenvironment, has recently been reported to affect the prognosis of Hodgkin lymphoma (HL). We aimed to evaluate its role in our patient cohort (n = 100) by utilizing a routine immunohistochemistry method on whole tissue sections and a semiquantitative method for CD68 scoring. Clinical data were taken from medical records. Correlation with baseline characteristics, attainment of complete remission (CR), progression-free survival (PFS) and disease-specific survival (DSS) was done by categorical analysis using different cut-offs of CD68 score and also by taking absolute CD68 score as a continuous variable. There was no significant association between levels of CD68 expression and baseline characteristics or CR after primary therapy. CD68 score (neither categorical nor absolute continuous values) also did not predict for any difference in PFS or DSS. We conclude that CD68 TAM marker does not have prognostic value in HL.